A propensity score matching analysis of dasatinib and nilotinib as a frontline therapy for patients with chronic myeloid leukemia in chronic phase. Issue 21 (10th August 2016) - Takahashi, Koichi; Kantarjian, Hagop M.; Yang, Yulong; Sasaki, Koji; Jain, Preetesh; DellaSala, Sara; Ravandi, Farhad; Kadia, Tapan; Pemmaraju, Naveen; Daver, Naval; Borthakur, Gautam; Garcia‐Manero, Guillermo; et al.
Abstract : BACKGROUND: Both dasatinib and nilotinib are approved frontline therapy for chronic myeloid leukemia in chronic phase (CML‐CP) based on randomized trials compared with imatinib. However, no head‐to‐head comparison of dasatinib and nilotinib has been conducted in patients with newly diagnosed CML‐CP. METHODS: The authors conducted a propensity score (PS) matched comparison of patients with CML‐CP who received frontline therapy with either dasatinib (N = 102) or nilotinib (N = 104) under the respective phase 2 trials conducted in parallel. RESULTS: PS matching resulted in 87 patients from each trial being matched for pretreatment characteristics. The 3‐month BCR‐ABL1/ABL1 ratio <10% rate was 93% with dasatinib and 94% with nilotinib ( P = .25); the rates of major molecular response at 12 months were 77% and 85%, respectively ( P = .13); and the rates of molecular response with 4.5‐log reduction in the ratio at 36 months were 66% and 64%, respectively ( P = .96). All other clinically relevant responses were similar between the 2 treatment cohorts. The 3‐year probability of event‐free survival was 89% among the patients who received dasatinib and 87% among those who received nilotinib ( P = .99), and the corresponding 3‐year overall survival probabilities were 99% and 93%, respectively ( P = .95). No statistical difference was observed between the dasatinib and nilotinib groups in any of the other survival endpoints. The treatment discontinuation rate also was similar between the 2 cohorts (dasatinib group, 18%; nilotinib group, 19%; P = .82). CONCLUSIONS: In a PS‐matched cohort of patients with newly diagnosed CML‐CP, dasatinib and nilotinib offer similar response and survival outcomes. Both drugs can be considered reasonable standard‐of‐care options as first‐line therapy for patients with CML‐CP. Cancer 2016;122:3336–3343 . © 2016 American Cancer Society . Abstract : This propensity score matching analysis of parallel phase 2 trials indicates that both dasatinib and nilotinib offer equivalent response rates and long‐term outcomes in patients with chronic myeloid leukemia in chronic phase when used as a frontline therapy. The results suggest that both treatment options are reasonable choices as frontline therapy, and the choice of drug can be made based on factors like toxicity profiles, comorbidities, physicians' experience, and treatment schedule.